O espaço da cultura em Araxá: entre o esquecimento e o espetáculo - Ferreira, Letícia Bemfica (2021)
Araxá, a city in the interior of Minas Gerais, with a population of 102,238 inhabitants (IBGE - 2015), was one of the first municipalities established in its region and, therefore, acquired great importance in the late 19th and early 20th centuries. In the 1940s, it was chosen by the Federal Government to host an expressive luxury hotel, which intended to make the city a cosmopolitan resort at the height of the seaside cities in Europe. From then on, several state and federal investments were made to carry out renovations and new works in the city, aimed at attracting tourists and the exhibition of the “great work”. All this history was responsible for the unfolding of a tourist and cultural image of the city of Araxá that, since then, has been trying to be maintained, by public policies, focusing on two areas of the municipality: the Grande Hotel do Barreiro and the city center. However, as in other cities in Brazil and the world, Araxá has faced the dilemma between valuing its architectural heritage or “modernizing” itself through new constructions. Although there is a certain movement in the city for the conservation of its architectural assets, in most cases, it is done through palliative and ineffective measures. Thus, aiming at the identification and exposure of Araxá’s cultural and tourist potential, this work focuses on the study of the set of cultural facilities in the central area, considering the plastering of old buildings in the face of enthusiasm for new constructions. The objective is to understand the process of idealization of this equipment and the associated cultural programming in its creation process, and to identify the reasons that separate them from the current cultural scene in the city. Also part of this discussion is the question of the continuous reformulation of the city based on the analysis of new architectural and urban projects that seek to preserve the progressive image of the municipality. In addition to analyzing the real need for these developments in view of the possibility of using other spaces, which are part of the city’s heritage, it is a social responsibility and the role of the architect to care for the marks of experience and the memory of the population, which has been left out due to the spectacle in which these new architectural works are involved. This work is part of the research project “Art, Architecture and City” and intends to contribute, in the study of the cultural scenario of the medium cities of the Triângulo Mineiro and Alto Paranaíba, from the survey and study of their cultural equipment.